Trans-europeanising public spaces in Europe - Sicakkan, Hakan G. (Javnost (Ljubljana), 2012)
Are there any trans-border interactions and networking patterns, any common systems of competing political discourses, and/or any common channels, platforms, or arenas of communication or action that can be regarded as the beginnings of a European public sphere? If so, how is this embryonic European public sphere being structured? Based on a comparative analysis of discursive configurations and networking patterns of more than 240 civil society organisations in sixteen European countries and eight European civil society networks, this article finds discursive gaps between the views of member state-level and European-level civil society organisations on diversity, the future of the EU polity, and who they see as their legitimate addressees. Networking patterns indicate this gap is not only in discourses but also in interactions. Considering the current segmentation along national lines, this may imply the beginnings of a development toward the emergence of a horizontally and vertically segmented European public sphere.
Keywords: Javna sfera; Public sphere; Europe; Evropa; civil society; civilna družba; mreženje; communication; komuniciranje; družbena omrežja